FIRE SYMBOLISM IN THE HOLY QUR’ÓN ANALYSIS OF CONTRARY CONNOTATION - Dr. Sardar Muhammad (Hamdard Islamicus, 2021)
The study of Symbolism not only helps to develop better understanding of the meanings of the Qur’Énic themes but also promotes Qur’Énic literature. This article analyses “fire” as a Qur’Énic symbol that represents a variety of literary and contextual meanings and interpret all its indications discussed in the precious text of Holy Qur’Én. The significance of fire symbolism can be evaluated from its usage in the Qur’Énic text more than any other symbol. It has a unique position in the Qur’Énic style to signify directly conflicting concepts. To assimilate opposing connotations of the “fire” in different situations, Zepetnek’s model of ideological inclusion (theory of comparative literature) has been followed. This is a model that allows the acceptability of diversified literary and contextual meanings of a single term. This model is adapted by various researchers and its adaptability, appropriateness and practicability is overall accepted. Thus, this model is apt for verifying different meanings of the “fire” from the text of Holy Qur’Én like, cool and hot, war and peace (Safety), comfort and torment, creation, and annihilation of Jinn, sacrifice and punishment, guidance and misguidance, blessing and infliction, construction and destruction, life, and death. In view of this model, the Qur’Énic text having “fire” symbolism and its contrary connotation has been observed.